Phase equilibria modelling of retrograde amphibole and clinozoisite in mafic eclogite from the Tso Morari massif, northwest India: constraining the P–T–M(H2O) conditions of exhumation. (28th April 2014) - Palin, R. M.; St‐Onge, M. R.; Waters, D. J.; Searle, M. P.; Dyck, B.
Abstract Phase equilibria modelling of post‐peak metamorphic mineral assemblages in (ultra)high‐P mafic eclogite from the Tso Morari massif, Ladakh Himalaya, northwest India, has provided new insights into the potential behaviour and source of metamorphic fluid during exhumation, and constrained the P–T conditions of hydration. A series of P–M(H2O) pseudosections constructed in the Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O (NCKFMASHTO) system show that a number of petrographically distinct hydration episodes occurred during exhumation from peak P–T conditions (~640 °C, 27–28 kbar), resulting in the formation of abundant compositionally zoned amphibole and minor clinozoisite poikiloblasts at the expense of a peak assemblage dominated by garnet and omphacite. Initial hydration is interpreted to have occurred as a result of the destabilization of talc following isothermal decompression to ~23 kbar, which led to the formation of barroisite–winchite amphibole core domains. An episode of fluid infiltration from an external source at ~19 kbar, with or without syn‐decompressional cooling to ~560 °C, resulted in further barroisitic–winchitic amphibole growth, followed by the formation of clinozoisite poikiloblasts. Continued buoyancy‐driven exhumation to the base of the lower crust is constrained to have taken place with no additional fluid input. A final hydration event is characterized by the formation of magnesiohornblende rims on the barroisite–winchite cores, with the former interpreted to have formed during later prograde overprinting in the middle crust associated with the final stages of exhumation. Notably, the vast majority of externally sourced H2O, comprising just over half of the current bulk rock fluid content, was added during this later hydration event. In a middle crustal setting, this is interpreted as the result of devolatilization reactions occurring in migmatitic host orthogneiss and/or metasedimentary units, or following the crystallization of partial melt.